PENGARUH PROMOSI, TINGKAT SUKU BUNGA, DAN LOKASI MELALUI KUALITAS PELAYANAN TERHADAP KEPUTUSAN BERTRANSAKSI PADA PD. BPR BANK DAERAH KARANGANYAR - Pibrina, Toni Erlangga Wahyu (-)
This study aims to determine and analyze empirically the influence of promotion, interest rates, and location through the quality of service to the decision to transact on PD. BPR of Bank Daerah Karanganyar. The analytical technique used is by using instrument test which includes validity test and reliability test, linearity test, regression analysis, path analysis, t test, F test, coefficient determination test and correlation analysis. Hypothesis Test Result: Promotion has a significant effect on customer service quality. The interest rate has a significant effect on the quality of customer service. Location has a significant effect on customer service quality. Promotion has a significant effect on customer transaction decisions. Interest rates have a significant effect on customer transactions decisions. Location has significant effect on customer transaction decision. The quality of service has a significant effect on the transaction decision of the Customer. F test results can be concluded together promotional variables, interest rates, location and quality of service affect the decisions of customer transactions in PD. BPR of Bank Daerah Karanganyar. The total R2 value of 0.755 means that the decision to transact customers in PD. The BPR of Bank Daerah Karanganyar is explained by promotion variable, interest rate, location and service quality of 75.5% and the remaining 24.5% described other variables outside the research model as an example of organizational culture, organizational climate and motivation. The results of path analysis show that promotion, interest rates and location are effective through direct line. And path analysis shows that interest rate has the most dominant influence in improving transaction decision in PD. BPR of Bank Daerah Karanganyar. Keywords          : Promotion, Interest Rate, Location, Service Quality, Transaction Decision